Analisis Efektivitas Sistem Informasi Akuntansi pada Verifikasi Pertanggungjawaban Uang Muka (PJUM) dan Reimbursement - Salsabil, Yasmin Inas; Yulianti Raharjo (Forum Kerjasama Pendidikan Tinggi, 2025)
This study aims to analyze the effectiveness and efficiency of implementing an accounting information system in the verification process of advance payment accountability (PJUM) and reimbursement at PT Petrokimia Gresik by utilizing the Web Uang Muka (WUM) system integrated with the System Application and Product in Data Processing (SAP). A descriptive qualitative approach was employed, using primary data collected through observation, an interview with a key informant, and documentation. The results indicate that the implementation of WUM and SAP has enhanced the effectiveness of the verification process, which was previously conducted manually using hardcopy documents - an approach that was time-consuming and prone to errors. This study highlights the importance of digitalization in financial management to improve both effectiveness and accountability